2017
DOI: 10.1007/s13346-016-0353-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism governing the transcriptional regulation of ABC transporters in MDR cancer cells

Abstract: P-glycoprotein (P-gp/ABCB1) and multidrug resistance-associated protein 1 (MRP1/ABCC1) are the main drug efflux transporters associated with treatment failure in cancer. Much attention has been focused on the molecular mechanisms regulating the expression of these transporters as a viable approach for identifying novel drug targets in circumventing cancer multidrug resistance (MDR) clinically. In this paper, we examine the role of miR-326 in the context of its intercellular transfer between cancer cells by ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…They operate as signaling vectors in the intercellular transfer of functional P‐gp from drug‐resistant to drug‐sensitive cells . Furthermore, EVs consolidate the MDR phenotype by incorporating and transferring functional nucleic acids species and effectively ‘re‐template’ the transcriptional landscape of recipient cells . P‐gp containing EVs have also been shown to confer a parallel resistance pathway through a capacity for active drug sequestration .…”
Section: Proteins Regulating Classical Mdrmentioning
confidence: 75%
See 1 more Smart Citation
“…They operate as signaling vectors in the intercellular transfer of functional P‐gp from drug‐resistant to drug‐sensitive cells . Furthermore, EVs consolidate the MDR phenotype by incorporating and transferring functional nucleic acids species and effectively ‘re‐template’ the transcriptional landscape of recipient cells . P‐gp containing EVs have also been shown to confer a parallel resistance pathway through a capacity for active drug sequestration .…”
Section: Proteins Regulating Classical Mdrmentioning
confidence: 75%
“…[13,50,170,177] Furthermore, EVs consolidate the MDR phenotype by incorporating and transferring functional nucleic acids species and effectively 're-template' the transcriptional landscape of recipient cells. [170,177,178] P-gp containing EVs have also been shown to confer a parallel resistance pathway through a capacity for active drug sequestration. [49] Intriguingly, MV-mediated transfer of P-gp appears to be tissue selective-breast cancerderived MVs only transferred the MDR protein to malignant breast cells.…”
Section: P-glycoprotein-associated Proteins and Mdr Acquisitionmentioning
confidence: 99%
“…Since several antipsychotic and anticonvulsants are considered substrates for P-glycoprotein (P-gp), it occurs that they are thrown out from the brain into the blood, which is an obstacle for brain accumulation [85]. ABC transporters have a key role in this kind of resistance [86]. They actively carry chemicals crossing biological membranes contributing to their disposal [87].…”
Section: Cannabinoids and Efflux Pumps In The Blood-brain Barriermentioning
confidence: 99%
“…In addition to transferring P‐gp protein to recipient cells, many resistant lines can produce EVs carrying MDR1 (ABCB1) or MRP1 (ABCC1) mRNA which can be transferred into sensitive cells to induce resistance . A recent study highlighted the complexity of relationship between mRNAs and miRNAs delivered using leukemia cell line CCRF‐CEM and its multidrug resistant derivatives VLB 100 and E 1000 . The authors showed that ABCB1 (also known as MDR1 ), ABCC1 (also known as MRP1 ), and miR‐326 can all be delivered in EVs, but that expression of ABCB1 dominates while miR‐326 represses ABCC1.…”
Section: Transfer Of Ev Rna Can Cause Transfer Of Drug Resistancementioning
confidence: 99%
“…[61,66,69,75,85] A recent study highlighted the complexity of relationship between mRNAs and miRNAs delivered using leukemia cell line CCRF-CEM and its multidrug resistant derivatives VLB 100 and E 1000 . [92] The authors showed that ABCB1 (also known as MDR1), ABCC1 (also known as MRP1), and miR-326 can all be delivered in EVs, but that expression of ABCB1 dominates while miR-326 represses ABCC1. If ABCB1 is knocked down then miR-326 represses ABCC1 less efficiently, suggesting a complex interplay between RNA delivered in EVs.…”
Section: Mrna and Long Noncoding Rnasmentioning
confidence: 99%